Representasi Konflik Keluarga Dalam Film Uang Panai Maha(r)l 2 - Mandi, Charmalita Citra Maharani; Putra Agung Mulyana (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
family conflict is portrayed in the film Uang Panai Maha(R)l 2 using Roland Barthes' semiotic framework. The film reflects the social reality of the Bugis-Makassar community, which highly upholds cultural values, particularly regarding arranged marriage, family honor, and the significant role of parents in their children's lives. The main objective of this research is to understand how family conflict is represented through visible and spoken symbols within the film’s narrative. This research employs a descriptive qualitative method by analyzing semiotic elements in several scenes that depict conflict, such as forced marriage, intergenerational differences, and the pressure of tradition against personal desires. The analysis is conducted through the three levels of meaning proposed by Barthes: denotation, connotation, and myth. The results show that Uang Panai Maha(R)l 2 illustrates the tension between traditional values and modern realities, which still occur within family life in Indonesia.